Evaluating risk, exposure, and detection capabilities for chemical threats in water. Issue 15 (3rd August 2022) - Pfohl, Marisa; Silvestri, Erin; Lipscomb, John C.; Snyder, Emily; Willison, Stuart
ABSTRACT: The unexpected release of chemicals into the environment requires estimation of human health risks, followed by risk management decisions. When environmental concentrations of toxicants are associated with adverse health risks, the limit for analytical measurement needs to be at or below the risk threshold. The aim of this study was to assess chemical contaminants that have the potential to produce acute adverse human health impacts following oral consumption of contaminated drinking water. The U.S. Environmental Protection Agency's (EPA) Candidate Contaminant List, version 4 (CCL4) and EPA's Selected Analytical Methods (SAM) document were screened to identify 24 chemicals that exist as a solid or liquid at room temperature, with acute oral LD50 (lethal dose in 50% of the test population) values < 500 mg/kg-d and water solubility > 500 mg/L at ambient temperature. While these screening criteria were used to identify prioritized needs for targeted research, it does not imply that other chemicals on the CCL4 and SAM lists are not issues in acute and chronic exposures. Of these 24 most toxic and most soluble chemicals, this evaluation identified 6 chemicals (2-chlorovinylarsonous acid, lewisite, N-nitrosopyrrolidine, N-nitrosodiethylamine, 3-hydroxycarbofuran, and triethylamine) lacking either sufficient toxicity value information or analytical sensitivity required to detect at levels protective against adverse effects in adults for acute exposures. This assessment provides an approach for gap identification and highlights research needs related to water contamination incident involving these six priority chemicals.